Getting a Life: Cinematic Representations and Critical Refractions of the Chevalier de Saint-George - Elson, Christopher (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2025)
In this commentary, I briefly consider, for context, a number of short films focused on the Chevalier Saint-George and films in which the figure of the Chevalier has appeared, before focusing on the 2023 feature-length biopic, Chevalier, directed by Steven Williams. These reflections are focused on the continuities between period piece films, biographical films and adaptations. A term borrowed from French poetics, "ineffacement," helps us to consider the film artist's double duties to their own artistic license and personal engagements, on the one hand, and on their various epistemological and ethical obligations to the historical source material on the other. Chevalier does not succeed as a film in part because it fails to present viewers with the dilemmas of such balancing or to show much evidence of having even considered them. The film does show the renewal of interest in the figure of the Chevalier and promises more attempts to do justice to this inspiring historical character.